Metal‐Free 2D/2D Heterojunction of Graphitic Carbon Nitride/Graphdiyne for Improving the Hole Mobility of Graphitic Carbon Nitride - Han, Ying‐Ying; Lu, Xiu‐Li; Tang, Shang‐Feng; Yin, Xue‐Peng; Wei, Zhen‐Wei; Lu, Tong‐Bu (Advanced energy materials, 2018)
The design and synthesis of efficient metal‐free photoelectrocatalysts for water splitting are of great significance, as nonmetal elements are generally earth abundant and environment friendly. As a typical metal‐free semiconductor, g‐C3N4 has received much attention in the field of photocatalytic water splitting. However, the poor photoinduced hole mobility of g‐C3N4 restrains its catalytic performance. Herein, for the first time, graphdiyne (GDY) is used to interact with g‐C3N4 to construct a metal‐free 2D/2D heterojunction of g‐C3N4/GDY as an efficient photoelectrocatalyst for water splitting. The g‐C3N4/GDY photocathode exhibits enhanced photocarriers separation due to excellent hole transfer nature of graphdiyne and the structure of 2D/2D heterojunction of g‐C3N4/GDY, realizing a sevenfold increase in electron life time (610 μs) compared to that of g‐C3N4 (88 μs), and a threefold increase in photocurrent density (−98 μA cm−2) compared to that of g‐C3N4 photocathode (−32 μA cm−2) at a potential of 0 V versus normal hydrogen electrode (NHE) in neutral aqueous solution. The photoelectrocatalytic performance can be further improved by fabricating Pt@g‐C3N4/GDY, which displays an photocurrent of −133 μA cm−2 at a potential of 0 V versus NHE in neutral aqueous solution. This work provides a new strategy for the design of efficient metal‐free photoelectrocatalysts for water splitting. A metal‐free 2D/2D heterojunction of graphitic carbon nitride/graphdiyne on a 3D graphdiyne nanosheet array (g‐C3N4/GDY) is constructed for improving the hole transfer kinetics of g‐C3N4, in which g‐C3N4/GDY shows much higher photoelectron catalytic performance for water splitting than g‐C3N4 due to the high hole transfer rate in graphdiyne and ultrathin 2D/2D heterojunction of g‐C3N4/GDY.